Nucleosome positioning by the winged helix transcription factor HNF3 - Shim, Eun Yong (Cold Spring Harbor Laboratory Press, 1998)
Nucleosome positioning at genetic regulatory sequences is not well understood. The transcriptional enhancer of the mouse serum albumin gene is active in liver, where regulatory factors occupy their target sites on three nucleosome-like particles designated N1, N2, and N3. The winged helix transcription factor HNF3 binds to two sites near the center of the N1 particle. We created dinucleosome templates using the albumin enhancer sequence and found that site-specific binding of HNF3 protein resulted in nucleosome positioning in vitro similar to that seen in liver nuclei. Thus, binding of a transcription factor can position an underlying nucleosome core.